Chemical Composition Analysis, Antioxidant, and Antibacterial Activities of Eggplant Leaves. Issue 12 (10th November 2020) - Bouhajeb, Rim; Selmi, Salima; Nakbi, Amel; Jlassi, Ibrahim; Montevecchi, Giuseppe; Flamini, Guido; Zarrad, Imen; Dabbou, Samia
Abstract: Agricultural by‐products represent one of the biggest pollutants for the environment, therefore, investigating new sources for the extraction of bioactive compounds is a topic of great interest for the entire scientific community. This work is aimed at studying the chemical composition (pigments, phenolics, volatile compounds) and biological activities (antioxidant and antimicrobial properties) of young and mature leaves of five eggplant cultivars ( Solanum melongena L.) grown in Tunisia (Tizona, A1014, Nawel, A336, and Mirval). Pigment analysis showed no statistical variations between the two types of leaves, whereas higher levels of anthocyanins were recorded in young leaves of three out of five cultivars (24.7–52.8 mg 100 g −1 ). Total phenolic compounds (966.5–2072.6 mg 100 g −1 ) and o ‐diphenols (343.9–741.2 mg 100 g −1 ) contents varied significantly according to leaf age and cultivar. However, no statistically significant variation between young and mature leaves was found in flavonols and tannins content. As for volatile profiles, 62 constituents were characterized with non‐terpene derivatives (52.0–61.6 %) and apocarotenes (19.9–35.6 %) as major chemical classes. Regarding the antioxidant activity, methanol extracts of Tizona cultivar mature leaves displayed important antiradical properties using DPPH, ABTS, and phosphomolybdenum assays (IC50 0.1, 0.2 and 0.01 mg mL −1, respectively). With regards to reducing power determination, the most active extract was obtained from mature A1014 leaves. Further, young Mirval leaves proved to be significantly active from a bactericidal point of view against Candida albicans and Staphylococcus aureus of 3.1 mg mL −1 and 0.2 mg mL −1 MBC, respectively. In conclusion, eggplant leaves are a noteworthy source of antioxidant and antimicrobial compounds with potential use in the pharmaceutical, the cosmetics and the food industries. Abstract :